Archaeology and the politics of vision in a post-modern context - Thomas, Julian, 1959-; Jorge, Vítor Oliveira (Cambridge Scholars Pub., 2008)
Archaeology is intimately connected to the modern regime of vision. A concern with optics was fundamental to the Scientific Revolution, and informed the moral theories of the Enlightenment. And from its inception, archaeology was concerned with practice.